The single-dose application of interleukin-4 ameliorates secondary brain damage in the early phase after moderate experimental traumatic brain injury in mice - Walter, Johannes; Mende, Jannis; Hutagalung, Samuel; Alhalabi, Obada; Grutza, Martin; Zheng, Guoli; Skutella, Thomas; Unterberg, Andreas; Zweckberger, Klaus; Younsi, Alexander (International journal of molecular sciences, 2023)
Activation of the interleukin-4 (IL-4) pathway ameliorates secondary injury mechanisms after experimental traumatic brain injury (TBI); therefore, we assessed the effect of a therapeutic IL-4 administration on secondary brain damage after experimental TBI. We subjected 100 C57/Bl6 wildtype mice to controlled cortical impact (CCI) and administered IL-4 or a placebo control subcutaneously 15 min thereafter. Contusion volume (Nissl staining), neurological function (hole board, video open field, and CatWalkXT®), and the immune response (immunofluorescent staining) were analyzed up to 28 days post injury (dpi). Contusion volumes were significantly reduced after IL-4 treatment up to 14 dpi (e.g., 6.47 ± 0.41 mm3 vs. 3.80 ± 0.85 mm3, p = 0.011 3 dpi). Macrophage invasion and microglial response were significantly attenuated in the IL-4 group in the acute phase after CCI (e.g., 1.79 ± 0.15 Iba-1+/CD86+ cells/sROI vs. 1.06 ± 0.21 Iba-1/CD86+ cells/sROI, p = 0.030 in the penumbra 3 dpi), whereas we observed an increased neuroinflammation thereafter (e.g., mean GFAP intensity of 3296.04 ± 354.21 U vs. 6408.65 ± 999.54 U, p = 0.026 in the ipsilateral hippocampus 7 dpi). In terms of functional outcome, several gait parameters were improved in the acute phase following IL-4 treatment (e.g., a difference in max intensity of −7.58 ± 2.00 U vs. −2.71 ± 2.44 U, p = 0.041 3 dpi). In conclusion, the early single-dose administration of IL-4 significantly reduces secondary brain damage in the acute phase after experimental TBI in mice, which seems to be mediated by attenuation of macrophage and microglial invasion.
Veröffentlicht: 14. August 2023
Gesehen am 16.10.2023